2018
DOI: 10.1111/jocd.12706
|View full text |Cite
|
Sign up to set email alerts
|

Identification and integrated analysis of microRNA expression profiles in keloid

Abstract: This study revealed the profiling of miRNAs in keloid that are potentially implicated in the development of this disease and could serve as novel diagnostic and therapeutic target of keloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
(41 reference statements)
2
19
0
Order By: Relevance
“…Through applying the same approach, Zhong et al revealed that 264 miRNAs were significantly altered in keloid [32]. The miRNA-199a-5p, miRNA-21-5p, miRNA-214-5p, miRNA-424-5p, and miRNA-205-5p, were the high-frequency DE miRNAs and were mainly associated with MAPK and HIF-1 signaling pathway by KEGG enrichment analysis [32].…”
Section: Mirna Expression Profiles In Keloidmentioning
confidence: 99%
See 1 more Smart Citation
“…Through applying the same approach, Zhong et al revealed that 264 miRNAs were significantly altered in keloid [32]. The miRNA-199a-5p, miRNA-21-5p, miRNA-214-5p, miRNA-424-5p, and miRNA-205-5p, were the high-frequency DE miRNAs and were mainly associated with MAPK and HIF-1 signaling pathway by KEGG enrichment analysis [32].…”
Section: Mirna Expression Profiles In Keloidmentioning
confidence: 99%
“…Through applying the same approach, Zhong et al revealed that 264 miRNAs were significantly altered in keloid [32]. The miRNA-199a-5p, miRNA-21-5p, miRNA-214-5p, miRNA-424-5p, and miRNA-205-5p, were the high-frequency DE miRNAs and were mainly associated with MAPK and HIF-1 signaling pathway by KEGG enrichment analysis [32]. Besides, it was very meaningful that Luan et al characterized the miRNA expression profiling in the sera from 9 keloid patients and 7 normal controls, identifying the 37 DE miRNA [33].…”
Section: Mirna Expression Profiles In Keloidmentioning
confidence: 99%
“…Noticeably, Chao et al . (8) reported 264 miRNAs were significantly altered in keloid lesions compared with normal skin tissue. For example, miR-21 (9) and miR-199a-5p (10) were shown to participate in keloid proliferation, migration and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, analysis of the KEGG pathway between I group and N group revealed that all of the DEGs were primarily enriched in cytokine−cytokine receptor interaction and viral protein interaction with cytokine and cytokine receptor, re ecting that these pathways may affect keloid formation. A study by Zhong L et al identi ed that target genes were associated with the MAPK signaling pathway and HIF-1 signaling pathway [31]. Our study provides a new eld for the molecular study of keloids.…”
Section: Discussionmentioning
confidence: 63%
“…In all, 8 patients (5 keloid patients without in ammation other than the keloid mass and 3 keloid patients with in ammation besides the keloid mass) were randomly selected from the department of plastic surgery at Peking Union Medical College Hospital between January 2019 and March 2020. The information of keloid patients (gender, age) was collected, and the keloid's condition was assessed by modi ed Vancouver scar scale (mVSS) 31 according to the pigmentation, vascularity, pliability and height of the keloid lesions (Table 1). There were 4 male patients and 4 female patients in each group; their ages ranged from 18 to 37 years.…”
Section: Patients and Groupingmentioning
confidence: 99%